Analysis of educational sport's idea - Alberto Gómez Mármol; Alfonso Valero Valenzuela (Federación Extremeña de Balonmano; University of Extremadura, 2013)
This work aims to describe how sport can contribute to the full development of its practitioners, as well as introducing the distinction between two concepts that are often used interchangeably, although they have different connotations: school sport and sport in school age, serving this distinction as an introduction to the relationship between sport and education, studying the characteristics the sport should have and that distinguish it from other physical activities. Thus, the objetive is to clarify the concepts around the sport practice initiation. In order to that, a deep revision of the most important national and international bibliography about this topic has been done. Similarly, once made this analysis of school age sports practice, it's showed the position of the experts on initiation sports about how the first contact between the child and the sport he wants to practice must be, being possible to conclude that real experts in sport initiation able to guarantee a right orientation of this formation period are needed.